Protocol for a comparative cross-sectional study on characterisation of auditory impairment in sickle cell disease and sickle cell trait and its impact on health-related quality of life in Nigeria - Obiageli Nnodu; Titus S Ibekwe; Christine Rogers; Lebogang Ramma (BMJ Open)
Introduction Sickle cell disease (SCD) and sickle cell traits (SCT) are genetically inherited red blood cell disorders common among people of African descent. Nigeria has a high prevalence of SCD, with a prevalence of 2.28%–3% and SCT, 25%–30%. Poorly managed SCD and SCT can lead to sensorineural hearing loss and health-related quality of life (HRQoL) issues. This research aims to assess these possible complications of SCD and SCT in Nigeria.Methods and analysis The study will use a comparative cross-sectional design at study power 80% to investigate the association between SCD/SCT, hearing impairment and HRQoL. Participants will be divided into two groups: a cohort and a control group. Hearing levels will be assessed through audiometric assessments and categorised by type and severity of hearing impairments using WHO classifications. HRQoL will also be assessed using WHO Disability Assessment Schedule 2.0. Statistical analyses will be performed using the SAS V.9.4, with parametric or non-parametric analysis depending on the distribution. Relationship between key variables will be determined via correlational tests, χ2, Fisher’s exact test and multivariable logistic regression analyses.Ethics and dissemination The proposal has been fully reviewed and registered by the University of Cape Town’s Faculty of Health Sciences Human Research Ethics Committee (HREC REF 228/2022) and the University of Abuja Teaching Hospital Human Research Ethics Committee (HREC/PR/2020/08/007). Information dissemination will be through conferences, peer-review publication and personal communications. The Strengthening the Reporting of Observational Studies in Epidemiology statement will be followed in writing the manuscript.